2014
DOI: 10.1002/fld.3916
|View full text |Cite
|
Sign up to set email alerts
|

A high‐order compact finite‐difference lattice Boltzmann method for simulation of steady and unsteady incompressible flows

Abstract: SUMMARYA high‐order compact finite‐difference lattice Boltzmann method (CFDLBM) is proposed and applied to accurately compute steady and unsteady incompressible flows. Herein, the spatial derivatives in the lattice Boltzmann equation are discretized by using the fourth‐order compact FD scheme, and the temporal term is discretized with the fourth‐order Runge–Kutta scheme to provide an accurate and efficient incompressible flow solver. A high‐order spectral‐type low‐pass compact filter is used to stabilize the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…For the higher kinematic viscosity ν = 10 −2 , the order of the accuracy of the solution is obtained 3.2 and it may be due to the compressibility errors because the characteristics velocity u 0 = 0.01 is not small enough here. It has been shown that the CFDLBM can lead to a more accurate solution compared with the analytical solution by considering a small characteristics velocity . Herein, the grid refinement study of the decaying double shear wave is also performed for ν = 10 −2 with the smaller characteristics velocity u 0 = 0.001 and the fourth‐order accuracy of the solution for this condition is indicated in Table (b).…”
Section: Numerical Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…For the higher kinematic viscosity ν = 10 −2 , the order of the accuracy of the solution is obtained 3.2 and it may be due to the compressibility errors because the characteristics velocity u 0 = 0.01 is not small enough here. It has been shown that the CFDLBM can lead to a more accurate solution compared with the analytical solution by considering a small characteristics velocity . Herein, the grid refinement study of the decaying double shear wave is also performed for ν = 10 −2 with the smaller characteristics velocity u 0 = 0.001 and the fourth‐order accuracy of the solution for this condition is indicated in Table (b).…”
Section: Numerical Resultsmentioning
confidence: 86%
“…It indicates that the boundary conditions imposed on the sphere wall based on the local distribution function with the extrapolation of the pressure (approximate BCs) do not affect the accuracy of the solution. It should be note that for the present numerical approach based on the compact finite‐difference LBM, the effects of two different procedures for implementing boundary conditions, namely, approximate and physical boundary conditions, are applied and assessed for 2D flow problems and it has been indicated that the accuracy of the solution is not affected by using these two procedures for the boundary conditions implementation and they give the same results.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some high‐order compact finite difference schemes have been developed for incompressible Navier‐Stokes (N‐S) equation or lattice Boltzmann equation to obtain the numerical solutions with good resolution characteristics and smaller computational stencil size. For example, Hejranfar and Ezzatneshan applied a high‐order compact scheme to the lattice Boltzmann method to solve incompressible flows . Different from the primitive variable formulation and the vorticity formulation, the use of the pure stream function or stream function‐velocity formulation of incompressible N‐S equation, in which the stream function and its first‐order partial derivatives (velocities) are taken as the unknown variables, is attractive because the boundary conditions of stream function and velocities are generally known and are easy to implement computationally.…”
Section: Introductionmentioning
confidence: 99%
“…The LBM studies the fluid flow with mesoscopic physics in which the particles 3 interpolation-or differential-type schemes [9][10][11]. These approaches eliminate the instability problem of the LBM with decoupling the time and space discretizations [12].…”
Section: Introductionmentioning
confidence: 99%